2016
DOI: 10.1016/j.exer.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGFβ cell signaling for limbal explant culture in serumless, defined xeno-free conditions

Abstract: Outgrowths of limbal epithelium by explant culture are used to treat limbal stem cell deficiency (LSCD). The explant culture medium is always complemented with serum, a complex solution which includes TGFβ. Since TGFβ is a cytostatic effector for epithelial proliferation we examined its effect on these cultures. Limbal biopsies were set on explant culture in DMEM/F12 with 5 ng/ml EGF and cholera toxin (ChT), ITS, and 5 % FBS, henceforth SHEM or a) SHEMSB = SHEM plus SB431542 an inhibitor of TGFβ signaling; b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Zamudio and collaborators have proposed the use of TGF-β inhibitors (SB431542 or A-83-01 [190]) as a means to promote stem cell proliferation [191]. Limbal stem cell deficiency (LSCD) is a devastating corneal pathology that arises from the depletion of limbal epithelial stem cells (LESCs) that reside in the limbus and are crucial for maintaining corneal epithelial turnover and transparency.…”
Section: Therapeutic Targets For Tgf-β Signaling Based Therapiesmentioning
confidence: 99%
“…Zamudio and collaborators have proposed the use of TGF-β inhibitors (SB431542 or A-83-01 [190]) as a means to promote stem cell proliferation [191]. Limbal stem cell deficiency (LSCD) is a devastating corneal pathology that arises from the depletion of limbal epithelial stem cells (LESCs) that reside in the limbus and are crucial for maintaining corneal epithelial turnover and transparency.…”
Section: Therapeutic Targets For Tgf-β Signaling Based Therapiesmentioning
confidence: 99%
“…prion disease), the development of tumorigenic effects, and immune reactions. 25 , 34 , 49 , 50 Furthermore, in order to protect public health when transplanting processed medical products into humans, these techniques must be performed under good laboratory practices, a requirement which has been passed into law in many European countries. 39 , 43 , 51 …”
Section: Introductionmentioning
confidence: 99%
“…The studies in the ocular surface epithelia have been facilitated by the remarkably high levels of ABCG2 expressed by the cells of the limbal outgrowth [14, 15]. However, efflux rate measurements in cells expressing exclusively ABCG2 or ABCB1 have shown that JC1 can serve as substratum for either multidrug resistance (MDR) transporter [1618].…”
Section: Introductionmentioning
confidence: 99%